Emerging molecular imaging targets and tools for myocardial fibrosis detection. (28th December 2022) - Barton, Anna K; Tzolos, Evangelos; Bing, Rong; Singh, Trisha; Weber, Wolfgang; Schwaiger, Markus; Varasteh, Zohreh; Slart, Riemer H J A; Newby, David E; Dweck, Marc R
Abstract: Myocardial fibrosis is the heart's common healing response to injury. While initially seeking to optimize the strength of diseased tissue, fibrosis can become maladaptive, producing stiff poorly functioning and pro-arrhythmic myocardium. Different patterns of fibrosis are associated with different myocardial disease states, but the presence and quantity of fibrosis largely confer adverse prognosis. Current imaging techniques can assess the extent and pattern of myocardial scarring, but lack specificity and detect the presence of established fibrosis when the window to modify this process may have ended. For the first time, novel molecular imaging methods, including gallium-68 ( 68 Ga)-fibroblast activation protein inhibitor positron emission tomography ( 68 Ga-FAPI PET), may permit highly specific imaging of fibrosis activity . These approaches may facilitate earlier fibrosis detection, differentiation of active vs. end-stage disease, and assessment of both disease progression and treatment–response thereby improving patient care and clinical outcomes. Graphical Abstract: Graphical Abstract Myocardial fibrosis occurs when various forms of myocardial injury affect previously healthy myocardium. Various existing imaging techniques including cardiovascular magnetic resonance, computed tomography, echocardiography, and nuclear imaging (single-photon emission computed tomography and 18F-FDG PET) assess the extent and pattern of myocardium scar. However, they are not specific to fibrosis and detect established fibrosis that may no longer be modifiable with treatment. Novel molecular fibrosis imaging methods may for the first time allow highly specific imaging of fibrosis activity . Benefits over existing modalities may include detection of the earliest stages of fibrogenesis, differentiation between active and end-stage disease, assessment of response to treatment in vivo as well as determination of the anti-fibrotic potential of existing and novel agents. These new techniques remain under investigation to determine their clinical utility. CMR images of myocardial infarction courtesy of Dr Trisha Singh. 68 Ga-FAPI-04 Images courtesy of Dr Zohreh Varasteh .